Multiple prolapsing mullerian vaginal cysts mimicking cystocele and enterocele - Bagchi, Sipra; Gupta, Ashish Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Multiple vaginal cysts are rare. Large cysts may present as vaginal wall prolapse. Proper assessment by clinical examination (under anaesthesia if necessary) and by USG and/or MRI should be done before surgical planning. Complete excision of cyst wall is necessary to prevent recurrence. A 40 years old P1L1 presented with mass per vaginum associated with pain and dyspareunia. On examination third degree cystocoele and a large posterior vaginal wall cyst with enterocoele was seen. Ultrasonography revealed no remarkable finding. Examination under anaesthesia followed by cyst excision was planned. Preoperatively three cysts were found, one on anterior wall mimicking as cystocoele, two cysts over prolapsed posterior vaginal wall, of which one had already ruptured. All the three cysts were excised completely. Histopathology revealed Mullerian cyst. This was an unusual case of multiple Mullerian vaginal cysts.